Effect of silicon dioxide/nanoclay on the properties of jute fiber/polyethylene biocomposites - Rahman, Md Mizanur; Rahman, Md Rezaur; Sinin, Hamdan; Md Faruk, Hossen; Chang, Josephine Hui Lai; Fui, Kiew Liew (John Wiley and Sons Ltd, 2017)
In this study, (jute fiber)/polyethylene biocomposites were prepared by using a hot press machine. Jute fiber was investigated as a reinforcing filler material for producing structural composites with better environmental performance. The effects of clay and silica addition on the physical, mechanical, and thermal properties of (jute fiber)-reinforced polyethylene biocomposites with different fiber loadings (5, 10, 15, and 20 wt%) were investigated. The biocomposites were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, and thermogravimetric analysis. The composite surface area and pore volume were determined by using the Brunauer-Emmett-Teller equation. The mechanical properties were investigated by using a Universal Testing Machine. Because of Si-O-Si stretching vibration, the O-H group from 3,200 to 3,400 cm−1 disappeared. The scanning electron microscopy results proved that a significant difference among the composites was present due to the interfacial bonding between the fiber and the matrix.